Emission Transparency and Funding Strategy: Implications for Firm Value - Jihan Maharani; Nandita Ayuni Safitri (Journal of Applied Accounting and Sustainable Finance, 2025)
Purpose – This study aims to analyze the effect of Greenhouse Gas Emissions Disclosure and Debt Policy on Firm Value in companies listed on the Indonesia Stock Exchange for the period 2021-2024. This study is relevant given the increasing global attention to environmental issues and corporate funding strategies as important factors in creating company value.  Design/methodology/approach – The research uses a quantitative approach with panel data regression method through Random Effect Model (REM). Data was obtained from annual reports and corporate sustainability reports during the study period. The independent variables used are Greenhouse Gas Emissions Disclosure and Debt Policy, while the dependent variable is Firm Value proxied by Tobin's Q. Findings – The results showed that Greenhouse Gas Emissions Disclosure has a positive but insignificant effect on Firm Value, indicating that the market has not fully considered emissions disclosure in valuation. In contrast, Debt Policy has a positive and significant effect, in line with signaling theory, which suggests that funding decisions through debt are perceived as a signal of confidence in the company's prospects. Research limitations/implications – The research is limited to the 2021-2024 observation period and only uses two independent variables, so it does not include other factors such as profitability, company size, and governance. The practical implication is that management needs to strengthen emission disclosure transparency and manage debt policy sustainably in order to increase investor confidence. JEL : G32, M41, Q56